Peran Mahasiswa KKN dalam Pemberdayaan Potensi Lokal Melalui Pembuatan Plang Sosial dan Perbaikan Pos Kamling Desa Nglengkong Lor - Rohmat Hidayat; Nia Zhuni Ambarwati; Zulfa Nur Halimah; Angga Wijaya; Farhan Aditya Pratama; Kristopras Rolando Takanyuai; Yahdi Ardha Hanifan; Diva Hidar Agustyan (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study examines the impact of the Thematic Community Service Program (KKN Tematik) on rural development, particularly focusing on two main initiatives: the creation of social signage and the renovation of the village security post. The KKN Tematik program serves as a platform for students to contribute to local development through scientific knowledge and participatory approaches. The first initiative involved designing and installing various social signage, such as warnings for “Damaged Road,” “Detour,” and notices for “Obituary,” which played a significant role in improving public awareness about road safety and other community issues. The second initiative focused on renovating the village security post, thereby enhancing local safety infrastructure and encouraging a sense of collective responsibility for the community’s security. The methodology used was participatory, which involved engaging local residents in every phase of the project, from planning to implementation and evaluation. This ensured that the initiatives were not only relevant to the community but also received strong support from local stakeholders. The results highlighted several positive outcomes: a marked improvement in visual communication awareness, increased collective participation in village security, and a better understanding of the role of infrastructure in community well-being. Additionally, the program also contributed to the local economy by employing village workers and sourcing materials locally, which stimulated the regional economy. The success of these initiatives demonstrates that community-based interventions, even on a small scale, can have substantial social and economic impacts, and it also shows that such projects can encourage sustainable rural development by fostering collaboration, strengthening local infrastructure, and promoting community engagement.